Analisis Kelayakan Usaha Peternakan Ayam Kampung Di Desa Rondaman Jae Kecamatan Halongonan Timur Kabupaten Padang Lawas Utara - Ulina Hutasuhut; Ari Andani Nasution (Fakultas Pendidikan Ilmu Keguruan, Universitas Pahlawan Tuanku Tambusai, 2026)
Operating a livestock business with a substantial herd size requires sound, professional planning and management—particularly regarding initial capital, daily operating costs, husbandry practices, product marketing, and accurate revenue and profit calculations. Challenges faced by small-to-medium-scale farmers include fluctuating feed prices (which account for 60–70% of total production costs), working capital availability, limited market access, and a lack of knowledge regarding business feasibility analysis. This study employs a quantitative descriptive method to provide a comprehensive overview of production cost components, revenue levels, and profitability in a household-scale free-range chicken farming business. Purposive sampling—a method of deliberately selecting a sample based on specific criteria established by the researcher—was utilized. The study relies on both primary and secondary data. The findings indicate that the